Injektion till katt – injektionsassocierad smärta samt injektioner i praktiken - Boström Johannesson, Madelene (2014)
Intramuscular injections to cats can generate strong reactions in some individuals while reactions of the same extent, according to the author, not always are recognized when using the subcutaneous route. The reactions are probably caused by fear, stress and/or pain. When the injection can generate pain one has to take that into account, which can be a limitation in treatment. It is well known that injections generate pain, but knowledge about the cause and processes of the injection-associated pain is limited. This is mainly due to the difficulty in finding objects to study pain on, high cost of use of laboratory animals and difficulty to obtain objective measurements. Although there is evidence that there may be a local muscle injury by intramuscular injection, it is not always that the extent of damage is related to the pain experienced.